2021
DOI: 10.3390/nu13072278
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Consumption of Beer (with and without Ethanol) and Menopausal Symptoms: Results from a Parallel Clinical Trial in Postmenopausal Women

Abstract: The menopausal transition can be a challenging period for women’s health and a trigger of uncomfortable symptoms. Beer is the main food source of isoxanthohumol, a precursor of 8-prenylnaringenin, the strongest phytoestrogen identified to date. As phytoestrogens are reported to reduce perimenopausal symptoms, we evaluated if a daily moderate consumption of beer with (AB) and without alcohol (NAB) could improve menopausal symptoms and modify cardiovascular risk factors. A total of 37 postmenopausal women were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
(105 reference statements)
1
14
0
Order By: Relevance
“…In postmenopausal women, SBP was not consistently reduced by the intake of (poly)phenols and both increases and decreases were reported. Nevertheless, some of the studies that indicated a decrease in SBP (even if not significant) reported reduction values between 2.0 and 11.0 mm Hg [26,29,32,37,44,45], suggesting that if these reductions were confirmed, the long term intake of (poly)phenols could have some impact in the cardiometabolic health of postmenopausal women but that this reduction would be more effective in women with only initial pre-hypertension [68] such as the significant reduction in SBP following the intake of blueberry powder containing mix (poly)phenols reported by Johnson et al [29]. Overall, it is tempting to hypothesize that (poly)phenols might be of help principally at early stages of the cardiometabolic disorders appearing in postmenopausal women but further studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In postmenopausal women, SBP was not consistently reduced by the intake of (poly)phenols and both increases and decreases were reported. Nevertheless, some of the studies that indicated a decrease in SBP (even if not significant) reported reduction values between 2.0 and 11.0 mm Hg [26,29,32,37,44,45], suggesting that if these reductions were confirmed, the long term intake of (poly)phenols could have some impact in the cardiometabolic health of postmenopausal women but that this reduction would be more effective in women with only initial pre-hypertension [68] such as the significant reduction in SBP following the intake of blueberry powder containing mix (poly)phenols reported by Johnson et al [29]. Overall, it is tempting to hypothesize that (poly)phenols might be of help principally at early stages of the cardiometabolic disorders appearing in postmenopausal women but further studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…From a methodological point of view, different elements may have affected the results and precluded a clear detection of potential benefits: (i) the small number of studies that could be selected and included in this review (21); (ii) the limited size of the sample populations involved in the studies, mostly between 15 and 20 per group (with a minimum size of 7 [32] to a maximum size of 120 participants per group [33]; (iii) differences in the source, nature and matrix of (poly)phenols (extracts, foods, beverages); (iv) presence of other constituents (i.e., fiber) which may have interfered with the effects of the (poly)phenolic compounds [54,55]; (v) not well designed control or placebo groups that should differentiate only in the (poly)phenols content [25,34,41,44]; and (vi) other general methodological specific issues such as the type of biological sample used (plasma, serum, fasting) or the analytical procedure applied. General recommendations regarding the RCTs have been thoroughly described indicating the need to improve the overall quality of the study design [56] and the presentation of the results in humans following intervention with bioactive compounds [57].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations